TREM-1 Expression on the Surface of Neutrophils in Patients With Visceral Leishmaniasis Is Associated With Immunopathogenesis - Bomfim, Lays Gisele Santos; Magalhães, Lucas Sousa; Rodrigues, Lorrany Santana; Barreto, Aline Silva; Santos, Camilla Natália Oliveira; Santos, Priscila Lima dos; Corrêa, Cristiane Bani; Fukutani, Kiyoshi Ferreira; Filho, Dalmo Correia; da Silva, Angela Maria; Lipscomb, Michael Wheeler; de Moura, Tatiana Rodrigues (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral leishmaniasis (VL) is a systemic chronic and potentially fatal disease for humans. Mechanisms related to the dysregulation of the inflammatory response may be involved in both the pathogenesis and prognosis of VL. Triggering Receptor Expressed on Myeloid Cells-1 (TREM-1) is a receptor constitutively expressed on neutrophils and monocyte subsets. The protein serves to regulate and amplify inflammatory responses. This study aimed to evaluate the expression profile of TREM-1 on the surface of neutrophils from patients with VL at varying timepoints during leishmanicidal treatment. For this purpose, neutrophils were isolated from the peripheral blood of patients with VL at different stages of treatment, which include 0, 7 and 30 days after treatment. Surface TREM-1 expression was assessed by immunophenotyping neutrophils population. In addition, association of TREM-1 expression on the surface of neutrophils with clinical and laboratory parameters and serum levels of inflammatory mediators were also evaluated. Results demonstrate a lower surface expression of TREM-1 in VL patients in absence of treatment. However, increased levels of TREM-1 expression were observed seven and thirty days after the start treatment, with levels similar to healthy controls. TREM-1 expression was directly correlated with lymphocyte and erythrocyte count, and indirectly correlated with spleen and liver size. Furthermore, elevated levels of TREM-1 expression were also correlated with lower serum levels of IL-22. Taken together, these results suggest that infection by L. infantum leads to depresses TREM-1 expression on the neutrophil surface and may contribute to the inflammatory imbalance that characterizes active VL disease.